Cross cultural adaptations and psychometric domains of Brazilian version of PROFILE PD for Parkinson’s disease - Swarowsky A.* (2017)
© 2016 Informa UK Limited, trading as Taylor & Francis Group.Purpose: The PROFILE PD scale was developed specifically to evaluate patients with Parkinson’s disease (PD) within the context of the International Classification of Functioning, Disability and Health, directly applied to physical therapy practice. The study aimed to translate and cross-culturally adapt the PROFILE PD scale to Portuguese-Brazil, and to analyze its psychometric domains. Methods: Fifty participants with PD participated in the study. We assessed the clarity of the Brazilian version of the scale by physiotherapists, presence of floor and ceiling effects, interrater and test–retest reliabilities, in addition to discriminant, concurrent (UPDRS) and construct validity, internal consistence, minimal detectable change (MDC), and responsiveness. Results: The scale was considered highly clear for physical therapists. The interrater ICC was 0.74 and Wk was 0.89 for the total score. For test–retest reliability, the total ICC score was 0.99. The analysis of concurrent validity showed the Spearman correlation between Brazilian version of PROFILE PD and UPDRS (ρ = 0.77; p < 0.001). Factor analyses demonstrated that the test comprises a single scale. Brazilian version of PROFILE PD was able to discriminate the subject with PD in mild and moderate stages, and in mild and severe stages. A high internal consistency was found (α = 0.99). MDC was 2.41 points and there were no floor and ceiling effects. Also, the scale was responsive to physical therapy intervention, with improvement in 8 points after two months (effect size = 0.85). Conclusion: The Brazilian version of PROFILE PD is an instrument reliable, valid, and responsive to physical therapy intervention, that can be used to quantify impairments and limitations in patients with PD and can provide an overall summary of the impact of disease, useful for physiotherapy practice. Implications for Rehabilitation PROFILE PD is a reliable and valid instrument to be applied in Brazilian Parkinson disease patients. This scale is design specially to be used in physical therapy practice within the contexts surrounding the International Classification of Functioning, Disability and Health. PROFILE PD was able to discriminate between patients in mild and moderate stages of disease which is difficult in clinical practice mainly because the scale used for this relies on balance and gait rather than a global profile.